The phenotypic spectrum of terminal and subterminal 6p deletions based on a social media-derived cohort and literature review - Eleana Rraku; Wilhelmina S. Kerstjens-Frederikse; Morris A. Swertz; Trijnie Dijkhuizen; Conny M. A. van Ravenswaaij-Arts; Aafke Engwerda (Orphanet Journal of Rare Diseases, 2023)
Abstract Background Terminal 6p deletions are rare, and information on their clinical consequences is scarce, which impedes optimal management and follow-up by clinicians. The parent-driven Chromosome 6 Project collaborates with families of affected children worldwide to better understand the clinical effects of chromosome 6 aberrations and to support clinical guidance. A microarray report is required for participation, and detailed phenotype information is collected directly from parents through a multilingual web-based questionnaire. Information collected from parents is then combined with case data from literature reports. Here, we present our findings on 13 newly identified patients and 46 literature cases with genotypically well-characterised terminal and subterminal 6p deletions. We provide phenotype descriptions for both the whole group and for subgroups based on deletion size and HI gene content. Results The total group shared a common phenotype characterised by ocular anterior segment dysgenesis, vision problems, brain malformations, congenital defects of the cardiac septa and valves, mild to moderate hearing impairment, eye movement abnormalities, hypotonia, mild developmental delay and dysmorphic features. These characteristics were observed in all subgroups where FOXC1 was included in the deletion, confirming a dominant role for this gene. Additional characteristics were seen in individuals with terminal deletions exceeding 4.02 Mb, namely complex heart defects, corpus callosum abnormalities, kidney abnormalities and orofacial clefting. Some of these additional features may be related to the loss of other genes in the terminal 6p region, such as RREB1 for the cardiac phenotypes and TUBB2A and TUBB2B for the cerebral phenotypes. In the newly identified patients, we observed previously unreported features including gastrointestinal problems, neurological abnormalities, balance problems and sleep disturbances. Conclusions We present an overview of the phenotypic characteristics observed in terminal and subterminal 6p deletions. This reveals a common phenotype that can be highly attributable to haploinsufficiency of FOXC1, with a possible additional effect of other genes in the 6p25 region. We also delineate the developmental abilities of affected individuals and report on previously unrecognised features, showing the added benefit of collecting information directly from parents. Based on our overview, we provide recommendations for clinical surveillance to support clinicians, patients and families.